Person-centered analysis of factors related to STEM students' global awareness - Sadan Kulturel-Konak (SpringerOpen, 2020)
Abstract Background Twenty-first century communication has changed how we connect to the rest of the world. Therefore, it requires the preparation of undergraduate science, technology, engineering, and mathematics (STEM) students who are capable of coping with problems on a global scale and who can participate effectively in a global economic and civic environment. Breathtaking ability to send vast amounts of data instantly and at times globally often translates to graduates entering the workforce needing to be aware of the global community. Hence, in this study, factors related to engineering students' global awareness have been explored so that higher education institutions may consider those factors when designing programs meant to influence this competence. The current study used a validated new instrument, based on a developmental model-the Model of Domain Learning (MDL)-to gauge engineering students' growth in global awareness. The presented research is studying the following research question: What is the relation between students' curricular and co-curricular experiences and levels of global awareness classified using MDL? Results Person-centered analyses were used to answer the research question. Four hundred twenty-five engineering students, who enrolled in 18 different engineering programs in a US land-grant university, participated in this study. The study found that engineering students' engagement in extra-curricular activities was correlated with an increase of their knowledge, strategic processing, and interest in the domain of global awareness. Conclusions Based on the data analysis, students' international experiences were positively related to not only their interest and knowledge but also their strategic processing predicted by the MDL. Moreover, engineering students' international experience and high academic engagement are important variables related to their perception of increased global awareness and improved skills for international careers. Hence, higher education institutions should consider making pedagogical interventions in their programs to effectively embed international experience into students' curriculum.